1986
DOI: 10.2307/1541915
|View full text |Cite
|
Sign up to set email alerts
|

FUNCTIONAL MORPHOLOGY AND SPECIES CHARACTERISTICS OF A LARGE, SOLITARY RADIOLARIANPHYSEMATIUM MUELLERI

Abstract: Physematium spp. and related genera of radiolaria (e.g., Thalassolampe and Actissd) are characterized by a large, limpid spherical cell body varying in cytoplasmic compactness, but characteristically possessing numerous small (ca. 3 nm dia.) symbionts held in fine radiating axopodia surrounding the large central capsulum. An analysis of the cytoplasmic organization of Physematium muelleri suggests that this organism has adapted to a pelagic existence by increasing surface area to enhance prey capture while con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Shallow 100 m 150 m λ tot (m −1 ) 0-100 m 0-150 m < 100 m 100-150 m λ Aul (m −1 ) (Anderson et al 1986), they have not been observed for Phaeodaria (Anderson et al 1986;. Furthermore, the results from the phaeodarian peak encountered on our P1106 cruise offer powerful constraints for testing this hypothesis.…”
Section: Stukel Et Almentioning
confidence: 74%
See 2 more Smart Citations
“…Shallow 100 m 150 m λ tot (m −1 ) 0-100 m 0-150 m < 100 m 100-150 m λ Aul (m −1 ) (Anderson et al 1986), they have not been observed for Phaeodaria (Anderson et al 1986;. Furthermore, the results from the phaeodarian peak encountered on our P1106 cruise offer powerful constraints for testing this hypothesis.…”
Section: Stukel Et Almentioning
confidence: 74%
“…Increasing its collection area sufficiently to meet its carbon supply (at a C : V ratio of 80 μ g C mm −3 ) would require a ~ ×80 increase in area or ~ ×9 increase in ESD. While extensive pseudopodial networks have been observed in some Rhizaria (Anderson et al ), they have not been observed for Phaeodaria (Anderson et al ; Nakamura and Suzuki ). Furthermore, the results from the phaeodarian peak encountered on our P1106 cruise offer powerful constraints for testing this hypothesis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation